Designing instructional animation for psychomotor learning: A conceptual framework - Lucas, Terry; Rahim, R.A (2015)
Research on the effectiveness of animated virtual human representation towards psychomotor learning is still lacking. Recent studies show that animation is effective in learning procedural tasks. Instructional animation is a form of animation designed to educate viewers. The purpose of this paper is to lay out a conceptual design framework for studies of the instructional animation design for psychomotor learning. Three theoretical approaches are considered in constructing the conceptual framework: (1) Learning Theories; (2) Instructional Video Design; and (3) Virtual Human Representation. Together, these theoretical fields complement one another and explain different viewpoints on this complex subject. Relating to earlier studies on types of visual representation may elucidate the ways in which animation can be applied for motor skill acquisition.